2015
DOI: 10.1158/0008-5472.can-14-1327
|View full text |Cite
|
Sign up to set email alerts
|

RSPO2 Enhances Canonical Wnt Signaling to Confer Stemness-Associated Traits to Susceptible Pancreatic Cancer Cells

Abstract: Cancer stem cells (CSC) present a formidable clinical challenge by escaping therapeutic intervention and seeding tumors through processes that remain incompletely understood. Here, we describe small subpopulations of pancreatic cancer cells with high intrinsic Wnt activity (Wnt high ) that possess properties indicative of CSCs, including drug resistance and tumor-initiating capacity, whereas cell populations with negligible Wnt activity (Wnt low ) preferentially express markers of differentiation. Spontan… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
52
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 61 publications
(58 citation statements)
references
References 46 publications
(53 reference statements)
6
52
0
Order By: Relevance
“…Our study indicated RSPO2 was significantly down-regulated in READ and kept the line with the published research, which demonstrates RSPO2 functions as a tumor suppressor; over-expression of it inhibits CRC cell proliferation and tumorigenicity [28]. RSPO2 is highly expressed in colon cancer stem cells and promotes the invasion of CRC cells through enhancing epithelial-mesenchymal transition [26]. The biological functions of RSPO2 in CRC and READ are unclear and the expression pattern of RSPO2 in READ regulated by DNA methylation modification and miRNA needs to be further investigated through experiments.…”
Section: Discussionsupporting
confidence: 78%
“…Our study indicated RSPO2 was significantly down-regulated in READ and kept the line with the published research, which demonstrates RSPO2 functions as a tumor suppressor; over-expression of it inhibits CRC cell proliferation and tumorigenicity [28]. RSPO2 is highly expressed in colon cancer stem cells and promotes the invasion of CRC cells through enhancing epithelial-mesenchymal transition [26]. The biological functions of RSPO2 in CRC and READ are unclear and the expression pattern of RSPO2 in READ regulated by DNA methylation modification and miRNA needs to be further investigated through experiments.…”
Section: Discussionsupporting
confidence: 78%
“…Ilmer et al showed that RSPO2-enhanced canonical Wnt signaling contributes to cancer stemness in pancreatic cancer [50]. Lgr5 and RSPO2 are also associated with tumor aggressiveness, lymph node metastases, and Wnt/β-catenin activation in human papillary thyroid cancer [51].…”
Section: Discussionmentioning
confidence: 99%
“…Take β -catenin as an example, β -catenin has been revealed to participate in the Wnt signaling pathway in various tumor subtypes [55, 56]. The initiation and progression of both pancreatic cancer and endometrial cancer have been confirmed to be associated with Wnt signaling pathway, implying that such two regulatory networks may have crosstalk and our extracted KEGG pathway (hsa05213) may actually contribute to the progression of pancreatic cancer [5759]. As for the other three important solid tumor associated pathways, two of them, renal cell carcinoma and colorectal cancer associated pathways ( hsa05211 and hsa05210 ), contain functional regulatory genes and pathways that have been reported to contribute to pancreatic cancer at the same time.…”
Section: Resultsmentioning
confidence: 99%